Performances of Planetary Magnetorheological Transmission Devices - Zhu, Xuli; Ma, Shanshan; Dong, Dong; Zong, Kefeng; Li, Liang; Teng, Guirong (Frontiers in Materials, 2022)
Magnetorheological transmission devices (MRTDs) are a type of power transmission device using magnetorheological fluids (MRFs) as the transmission medium, which have the advantages of rapid response and continuously adjustable output performances. A new type of structure of planetary MRTDs is proposed to improve the performances of MRTDs in this study. A planetary MRTD was fabricated, and the performances of it were tested on the self-made testing system. The experimental results show that the continuously variable transmission of MRTDs under constant torque can be realized by adjusting the excitation current. The output speed or torque can be adjusted by adjusting the control current when the input speed is constant. The output torque increases with the increase in the input speed when the excitation current is constant. The performances of the MRTD were analyzed according to the properties of MRFs in complex flow and magnetic field. MRFs in complex flow and magnetic fields can produce more stable and higher responses to external magnetic fields than being simple sheared; thus, the planetary MRTDs have better performances and are useful structures for the application of MRFs in transmission.